Sistem Pemasaran, Transaksi dan Persediaan Barang dengan Komputerisasi Berbasis Web - Handayani, Fanni (Jurnal Informatika Ekonomi Bisnis, 2020)
Azwa Perfume is a goods trading business. Goods that are traded are various types of perfume. At this time Azwa Perfume's trading income is difficult to grow with the lack of increasing variety of buyers. So this research was carried out to build a system that can introduce types of perfume globally and real time data processing. The method used is to build an online system by applying Economic Order Quantity (EOQ) and Reorder Point (RP) to maintain supply stability. The results of this study can further introduce the types of perfume online and buyers can place orders online. The inventory can be controlled at any time so that every buyer who needs a type of perfume can be served quickly and precisely. So this research really helps in marketing, sales transactions and controlling inventory very well.